Prevalence and Associated Metabolic Factors of Gallstone Disease in the Elderly Agricultural and Fishing Population of Taiwan - Hsi-Che Shen; Yi-Chun Hu; Yu-Fen Chen; Tao-Hsin Tung (Gastroenterology Research and Practice)
Purpose. To evaluate sex-related differences in the prevalence of and cardiovascular risk factors related to gallstone disease (GSD) in an elderly agricultural and fishing population of Taipei, Taiwan. Methods. The study sample consisted of 6511 healthy elderly participants (3971 men and 2540 women) who were voluntarily admitted to a teaching hospital for a physical checkup in 2010. The participants’ blood samples and real-time ultrasound fatty liver results were collected. Results. The prevalence of GSD in the study population was 13.2%, which increased significantly with population age (P<.0001). Women were associated with significantly higher GSD prevalence than men (14.8% versus 12.2%; for the chi-square test, P=.003). In a multiple logistic regression analysis, female sex, older age, and metabolic syndrome (MetS) were significantly associated with GSD. Multiple logistic regression analysis also revealed that obesity (odds ratio OR=1.26, 95% confidence interval (CI): 1.09–1.44) and metabolic factors (one or 2 versus none, OR=1.48, 95% CI: 1.08–1.76) were significantly associated with GSD in women but not in men. Conclusion. In the study population, female sex, older age, and MetS were associated with higher GSD prevalence. The population exhibited other sex-related differences.